2020
DOI: 10.1093/sleep/zsaa152
|View full text |Cite
|
Sign up to set email alerts
|

Largest scale dissociation of brain activity at propofol-induced loss of consciousness

Abstract: The brain is a functional unit made up of multi-level connected elements showing a pattern of synchronized activity that varies in different states. The wake-sleep cycle is a major variation of brain functional condition that is ultimately regulated by subcortical arousal- and sleep-promoting cell groups. We analyzed the evolution of functional MRI signal in the whole cortex and in a deep region including most sleep- and wake-regulating subcortical nuclei at loss of consciousness induced by the hypnotic agent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
1
12
0
1
Order By: Relevance
“…These results provide strong evidence that reductions in rCBF in the thalamus and precuneus/PCC is functionally related to decreased level of consciousness independently of nonspecific effects of anesthetic agents. Then, several recent fMRI studies have suggested that propofol decreased cortico-cortical connectivity in higher-order [88,[100][101][102]. In contrast, functional connectivity in lowlevel sensory cortices (e.g., sensorimotor network, visual and auditory networks) is preserved, consistent with the studies with midazolam reviewed above [88].…”
Section: Similar and Contrasting Neuroimaging Results From Studies Wisupporting
confidence: 74%
“…These results provide strong evidence that reductions in rCBF in the thalamus and precuneus/PCC is functionally related to decreased level of consciousness independently of nonspecific effects of anesthetic agents. Then, several recent fMRI studies have suggested that propofol decreased cortico-cortical connectivity in higher-order [88,[100][101][102]. In contrast, functional connectivity in lowlevel sensory cortices (e.g., sensorimotor network, visual and auditory networks) is preserved, consistent with the studies with midazolam reviewed above [88].…”
Section: Similar and Contrasting Neuroimaging Results From Studies Wisupporting
confidence: 74%
“…Specifically, the superior parietal lobule (SPL, BA7), dorsolateral prefrontal cortex (DLPFC, BA9, 46), and inferior parietal lobule (SMG, BA40) that started to change earlier in the present study are involved in conscious awareness (17,18), including attention, sensory perception, and integrating inputs from unimodal sensory regions (19)(20)(21)(22). The DMN is the crucial network of self-awareness and internal awareness (23). Therefore, the external awareness would be disrupted with the decreased activity of the FPN during the loss of consciousness induced by general anesthesia.…”
Section: Discussionmentioning
confidence: 64%
“…Previous EEG studies indicated that with increasing propofol concentration, the power spectrum shifts from a high-frequency, low-amplitude activity to a low-frequency, high-amplitude activity (5,7). However, power changes in beta of (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Hz and low gamma of (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) Hz frequency during propofol induction were inconsistent with previous studies (5,(8)(9)(10). In the present study, we found that in the transition from awake state to unconscious state, power in the global ECoG channels increased at lower frequency (< 46 Hz), and decreased at high gamma frequency.…”
Section: Discussionmentioning
confidence: 98%
“…In the last decade, multiple efforts have been made to characterize AAN, aiming to provide information to predict neurological outcomes in patients with severe brain injury and consequent DOCs 8 , 14 , 16 , 19 . The advancement of MRI techniques has allowed analysis of the anatomic and functional connectivity of the human brain 4 , 12 , 23 , 24 . In combination with the information acquired from DTI and BOLD, analysis of the AAN has revealed bidirectional connectivity between AAN nuclei in the brainstem and diencephalon and other multiple areas over the brain cortex 12 .…”
Section: Discussionmentioning
confidence: 99%